2022
DOI: 10.3390/ijerph19042438
|View full text |Cite
|
Sign up to set email alerts
|

Are Sports Champions Also Anti-Epidemic Heroes? Quantitative Research on the Influence of Sports Champions’ Demonstration Effect on the COVID-19 Epidemic in China

Abstract: What kind of role do sports champions play in the COVID-19 epidemic? Do they contribute to the mitigation of the epidemic by some pathway? In this paper, we empirically explore the influence and mechanism of the demonstration effect of sports champions upon the COVID-19 epidemic using COVID-19-related dataset of prefecture-level cities in China from 1 January 2020 to 17 March 2020. The two-way fixed effect model of econometrics is applied to estimate the result, the instrumental variable approach is adopted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In order to test the theoretical hypotheses, we performed ordinary least squares regression [ 11 , 43 , 47 , 49 ] to explore the effect of physical activity on COVID-19. To avoid biased estimators led by omitted variables, a two-way fixed-effects model, which is widely applied in the estimation of panel data [ 43 , 46 ], was used to control the time-invariant individual heterogeneity and the individual-invariant time heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to test the theoretical hypotheses, we performed ordinary least squares regression [ 11 , 43 , 47 , 49 ] to explore the effect of physical activity on COVID-19. To avoid biased estimators led by omitted variables, a two-way fixed-effects model, which is widely applied in the estimation of panel data [ 43 , 46 ], was used to control the time-invariant individual heterogeneity and the individual-invariant time heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, PA is beneficial to metabolic health as well as immune health, which decreases the risk of infectious complications [ 7 , 8 , 9 , 10 ]. Therefore, regular physical activity seems to be an effective measure for the prevention of viral infections—especially COVID-19 [ 11 , 12 ]. However, there remains a lack of sufficient, global, and in-depth theoretical analysis and empirical evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, timely and strict public health interventions have played a crucial role in the mitigation of the COVID-19 outbreak. Referring to Huang et al [ 77 ], we scored the public health measures implementation intensity of each city based on the epidemic prevention policy announcement issued by the health commission and converted it into a dummy variable according to the mean value. If the value was higher than the mean value, then the value was 1, indicating relatively strict prevention and control intensity; otherwise, the value was 0.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that population mobility does not mainly depend on the geographical distance between regions, but on the convenience of mobility, that is, the effective distance between regions [ 77 ]. Referring to Lin et al [ 59 ], we calculated the effective distance to Wuhan, the city with the most severe epidemic in China.…”
Section: Methodsmentioning
confidence: 99%